The Role of Storytelling in Brand Building: A Meta-Analysis - Armiani, Armiani; Nursansiwi, Dwi Arini (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to explore the impact of interactive storytelling on perception, brand authenticity And transparency among Generation Z on various digital platforms. Given that Gen Z has high expectations for brand authenticity and openness, interactive storytelling has emerged as an important strategy in modern digital marketing. Using a meta-analysis approach with a combination of quantitative and qualitative methods, this research examines previous studies that discuss interactive storytelling and its implications for consumer perceptions. The results of the quantitative analysis show that interactive storytelling has a significant positive effect on perception, brand authenticity And transparency, with variations in impact seen between different digital platforms. Qualitative analysis further highlights the specific aspects of interactive storytelling that Gen Z values ​​most, including direct interactions with brands and personalized experiences. This research contributes to the digital marketing literature by offering a comprehensive understanding of how interactive storytelling can influence consumer perceptions, while providing practical guidance for marketers in designing more effective strategies. Final recommendations suggest implementing storytelling that actively engages consumers to build deeper and more sustainable trust among Gen Z consumers.